Introducing IBM Z System Recovery Boost - Lascu, Octavian; Schouten, Paul; Nakajima, Kazuhiro (IBM redpaper., 2020)
In this IBM® Redpaper publication, we introduce System Recovery Boost, which is a new function of the IBM z15™. System Recovery Boost delivers substantially faster system shutdown, restart, and catching up with accumulated backlog of work after a restart.